PATH COEFFICIENT ANALYSIS IN WHEAT - SUIBHANI, GHULAM MAHBOOB; KHALIQ, IHSAN (Biological Sciences - PJSIR, 2022)
An eight parental diallcl cross was made to study the extent of variability, interrelationship, direct and indirect effects bet ween grain yield and its components. Genotypic variability coefficient was higher Ior grain yield as compared to other studied characters. Heritability estimates ranged from moderate (66.20%) to high values (96.95%). Number of grain per spike 1000 grain weight and plant height were positively and significantly correlated with yield except number of spikes per plant. Path coefficient indicated that except plant height the traits have positive direct effect on grain yield.